The stranger : Barack Obama in the White House - Todd, Chuck, 1972- (Little, Brown, 2014)
Barack Obama won the presidency in 2008 partly because he was a Washington outsider. But when he got to 1600 Pennsylvania Avenue, that distinction turned out to be double-bladed. NBC's award-winning Chief White House Correspondent Chuck Todd draws upon his unprecedented inner-circle sources to create a gripping account of Obama's tumultuous first term and campaign to win another.